The role of strategic Renewal in organizational immunity - analytical research in the Iraqi Ministry of Education - Mohammed Abdullah Ameen; Hossam Ali Mhaibes (Eximia, 2024)
The current study aims to demonstrate the role of strategic renewal in enhancing organizational immunity through strategic renewal mechanisms represented by (Reanimating, Rejuvenation, Venturing, and restructuring). The main idea of this study relates to the extent to which organizations’ immunity is achieved through strategic Renewal mechanisms, by measuring these dimensions with Organizational immunity represented by organizational learning, organizational memory, and organizational DNA. The study population was the headquarters of the Iraqi Ministry of Education, and the sample included (330) individuals from the upper, middle, and lower leadership levels. Several statistical methods were used to deal with the results of the questionnaire, especially the simple correlation coefficient (Pearson) and descriptive analysis methods using (SPSS.v23, AMOS.v25). The most important conclusion of the study was the presence of a clear and significant impact of strategic Renewal in building and designing the immune system of organizations.